CD3 and CD79A expression by cells of the rat gastric mucosa - Popko, S. S.; Yevtushenko, V. M.; Попко, Світлана Сергіївна; Євтушенко, Валентина Михайлівна (Запорізький державний медичний університет, 2018)
Background. The antigen exerting influence on fetus in the last 10 years have being increased actually. This fact is closely linked with immune stimulation reactions in fetus and neonatal. It's known that, antigenic fluxing in to fetus, is likely to cause premature out coming of T-cells from Timus and migration in to the different organs. As a result, the term of developing main structure components of organs is variate. An object of the study: a rat stomach in normal and after the intrauterine administration of the antigen at the 21st, 45th and 90th days of life.
Keywords: тези